KEDUDUKAN SERTIPIKAT HAK MILIK ATAS TANAH YANG TERDAFTAR ATAS NAMA SEORANG AHLI WARIS (Putusan Mahkamah Syar’iyah Nomor : 0220/Pdt.G/2015/MS-Tkn) - ABZA KARANESA (PREMISE LAW JURNAL, 2017)
ABSTRACT Generally, in the division of inheritance will be settled by deliberation, but if a dispute arises between an heir of the other heirs, then the division of inheritance is will be resolved through the courts As for problems raised in this research is the First: